2015 Long Island Systems, Applications and Technology 2015
DOI: 10.1109/lisat.2015.7160184
|View full text |Cite
|
Sign up to set email alerts
|

FPGA-based denoising and beat detection of the ECG signal

Abstract: In this work, an efficient digital system is designed using hardware to filter the Electrocardiogram (ECG) signal and to detect the QRS complex (beats). The system implementation has been done by using a Field Programmable Gate Array (FPGA). In the first phase of the hardware system implementation, Finite Impulse Response (FIR) filters are designed for preprocessing and denoising the ECG signal. The filtered signal is then used as the input of the second phase of the hardware implementation to detect and class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The performance of the implemented "ECG_AD_module" was compared with other arrhythmia detection system. The total number of registers utilized for the proposed design was 77.57 improved than the previous design [24].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The performance of the implemented "ECG_AD_module" was compared with other arrhythmia detection system. The total number of registers utilized for the proposed design was 77.57 improved than the previous design [24].…”
Section: Discussionmentioning
confidence: 88%
“…The proposed arrhythmia detection system designed based on FPGA from the results showed that it utilized less number of resources in terms of total number of pins, registers and memory bits when compared to previous design found from the literature. The proposed design when compared with most proven design [24] proved to be more efficient in terms of resource utilization, the results showed that the total registers are 792 when compared to that of the previous design [24] to be 3532. Total pins and memory bits are 43 and 51177, that in case of previous design [24] are 128, 131072 respectively.…”
Section: Fig62 Proposed Ecg-ad-module When Reset =0 Using Chip-smentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, deep learning methods have been widely utilized in face recognition and other classification problems [32,26,8,34,35,16,37] instead of classical methods [6,2]. These methods, can also be employed for the task of sketch-photo recognition problem by learning the relationship between the two modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Computer vision deals with acquiring, processing, and understanding images in order to solve different tasks. Computer vision has a wide range of applications including video gaming [16], in the food industry [17], robotics [18,19,20], biomedical [21,22], and many more [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41].…”
Section: Introduction 11 Problem Definitionmentioning
confidence: 99%